Pengaruh Job Insecurity, Stres Kerja, dan Beban Kerja terhadap Turnover intention PT Astra Honda Motor - Husnul Khatimah; Nur Indah Pratiwi (Optimal: Jurnal Ekonomi dan Kewirausahaan, 2023)
This research aims to determine the influence of job insecurity, work stress, and workload on turnover intention among millennial employees of PT Astra Honda Motor. This research uses a quantitative approach with primary data obtained through distributing questionnaires. The sampling technique uses a purposive sampling method involving all employees as the population. Data analysis was carried out using multiple regression to see the influence of each independent variable on turnover intention. The research results show that work stress has a positive and significant influence on turnover intention, while job insecurity and workload do not have a significant influence. These findings indicate that job stress is an important factor influencing employees' intention to leave the company, while job insecurity and workload do not have a significant influence in this context.